Effects of vegetation cutting on invertebrate communities of high conservation value Calluna upland peatlands. Issue 3 (8th October 2019) - Sanderson, Roy; Newton, Samuel; Selvidge, Jen
Abstract: Upland moors and bogs in the United Kingdom are peatlands of high nature conservation value, many designated under the European Union's Habitat Directive, with internationally important bird populations, which depend on abundant invertebrate populations when breeding. Moorland management in the United Kingdom traditionally employs controlled burning in 10–30 year rotations of heather, Calluna vulgaris, creating habitat mosaics of different species composition and physical structure. This can increase overall invertebrate biodiversity and abundance, for certain key invertebrate groups. Burning has potential negative environmental effects, including peat erosion and contamination of drinking‐water supplies. Rotational cutting of vegetation is now being trialled as an alternative to burning, but its long‐term effects on invertebrates are poorly understood. We surveyed invertebrates on a 16‐year chronosequence of rotational cutting on an extensive area of dwarf shrub vegetation on upland peat soils in Northern England. Invertebrate Simpson diversity was greatest on intermediate‐aged patches, and along edges between cut and uncut areas. Older patches, cut between 2000 and 2008, were dominated by ants (Hymenoptera‐Formicidae), plant‐feeding bugs (Hemiptera‐Auchenorrhyncha) and parasitic wasps (Hymenoptera‐Parasitica). Patches cut more recently, between 2009 and 2016, had significantly lower invertebrate abundance, and were dominated by predatory ground beetles (Coleoptera‐Carabidae), ants and harvestmen (Opiliones). There were significant relationships between vegetation and invertebrate community composition under both invertebrate sampling methods. We recommend that rotational cutting is used as the primary means of management, it should be undertaken in approximately 15–20 year rotations, in irregularly shaped mosaics, to maximise the benefits to invertebrates and associated wildlife. Abstract : Upland moors and bogs in the United Kingdom are of high conservation value for fauna and flora, and many are managed through rotational burns to create habitat mosaics. Burning can have negative environmental impacts therefore cutting of heather has been piloted over 15 years in Cumbria, UK, and effects on insects and plants investigated. We found strong associations between insect and plant diversity, highest on intermediate‐aged plots. Cutting appears to provide a viable alternative to burning to maintain biodiversity.